2011
DOI: 10.1152/ajpregu.00791.2010
|View full text |Cite
|
Sign up to set email alerts
|

Renal programming: cause for concern?

Abstract: Development of the kidney can be altered in utero in response to a suboptimal environment. The intrarenal factors that have been most well characterized as being sensitive to programming events are kidney mass/nephron endowment, the renin-angiotensin system, tubular sodium handling, and the renal sympathetic nerves. Newborns that have been subjected to an adverse intrauterine environment may thus begin life at a distinct disadvantage, in terms of renal function, at a time when the kidney must take over the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 158 publications
(191 reference statements)
4
150
1
1
Order By: Relevance
“…While not impacting baseline arterial pressure, recent studies have suggested that a low nephron number does increase the risk of developing hypertension in animals exposed to secondary adverse stimuli such as a highsalt diet (12). We hypothesized that if a low nephron endowment is associated with an increased risk for hypertension and its associated pathologies, then a high nephron endowment may act in an opposing, protective, manner.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While not impacting baseline arterial pressure, recent studies have suggested that a low nephron number does increase the risk of developing hypertension in animals exposed to secondary adverse stimuli such as a highsalt diet (12). We hypothesized that if a low nephron endowment is associated with an increased risk for hypertension and its associated pathologies, then a high nephron endowment may act in an opposing, protective, manner.…”
Section: Discussionmentioning
confidence: 94%
“…Yet the number of nephrons in human kidneys has been found to be highly variable, with a 13-fold range recently reported (10). A low nephron endowment has long been identified as a risk factor for the development of hypertension and chronic kidney disease (12,18,27), particularly in the presence of secondary insults, such as a high-salt diet (6,17,22). However, the converse hypothesis, that a high nephron number decreases the risk of hypertension and renal disease, has not been explored experimentally, despite the findings of a recent human autopsy study in which probability of presenting with hypertension was decreased in Caucasian Americans with a nephron endowment Ͼ876,300 compared with subjects with a lower nephron endowment (21).…”
mentioning
confidence: 99%
“…11,12 Moreover, the trajectory of the relationship between age and arterial pressure is influenced by birth weight and growth in childhood. 13 Indeed, in a recent large-cohort study, linear growth velocity (height) between 8 and 13 years in boys was shown to be positively associated with adult arterial pressure.…”
Section: Sex-related Differences In the Trajectory Of Arterial Pressumentioning
confidence: 99%
“…18 Animal studies have recapitulated these findings and allowed exploration of the underlying mechanisms, which are sexually dimorphic. 12,19 Testosterone has been clearly demonstrated to contribute to the programming of adult hypertension in growth-restricted male rat offspring. 20 Recently, this same group has defined a role for increased oxidative stress in determining kidney function and arterial pressure in growth-restricted male offspring, an effect that was reversed by antioxidant therapy.…”
Section: Sex-related Differences In the Trajectory Of Arterial Pressumentioning
confidence: 99%
“…Broadly, these studies showed that cardiovascular, renal, and metabolic disorders could all be programmed by undernutrition. 8 Although these malnutrition models still have significance in today's society, the high rates of obesity in the Western world, and urbanized regions of the developing world, have led to a shift in the field of programming from one of maternal undernutrition to one of maternal overnutrition. As the prevalence of maternal obesity rises, so too has the number of children at risk of fetal programming.…”
mentioning
confidence: 99%